Sensory and Functional Recovery after Suprafascial Free Flap in Foot and Ankle Reconstruction - Akaranuchat, Nutthawut; Kongkunnavat, Natthapong (Journal of Reconstructive Microsurgery Open, 2023)
Background The goals of foot and ankle defect reconstruction include weight-bearing and shearing tolerance, good mobilization, regaining protective sensation, and good contour for footwear fitting. This study reports the outcomes of foot and ankle defect reconstruction with suprafascial free flaps relative to sensory and functional recovery.Methods Eleven suprafascial free flaps were performed, which were supra-Scarpa fascial flaps in seven cases. Sensory recovery was assessed by Semmes-Weinstein monofilament test (SWMT), and functional outcomes were measured using the Foot and Ankle Ability Measure (FAAM) questionnaire at preoperative and subsequent visits.Results Eleven cases (age range: 21–83 years, seven males, mean body mass index: 24.8 kg/m2) were operated and the mean defect size was 109.8 cm2. The anterolateral thigh, medial sural artery perforator, and superficial circumflex iliac artery perforator flaps were used. The mean flap thickness was 0.8 cm. Average flap harvesting time and operative time were 83.9 and 452.0 minutes. Half of cases achieved 10 g SWMT (two cases regained baseline sensation) by 6-months post-operation, and all cases regained either 10 g SWMT or baseline sensation within 12 months. Significant improvement in the activities of daily living (ADL) and sports subscales was observed at 3 months (p < 0.05). Significant improvement in the global function rating scale for both ADL and sports was achieved by 6 months (p < 0.05). None experienced the recurrent ulcer.Conclusion Suprafascial free flap is a good reconstruction strategy for managing complex foot and ankle defects that yields favorable outcomes including adequate protective sensation and significant functional improvement.
Keywords: suprafascial free flap; reconstruction; sensation; functional outcomes; lower extremity